Meningkatkan Produktivitas Kewirausahaan Islam Melalui Pelatihan Berbasis Syariah untuk Siswa di Islamic Entrepreneur Boarding School di Purwakarta - Ratnawati, Nirdukita; Faruqi, Faris; Arsjah, Regina Jansen; Salfinnia, Masni; Nugraha, Ahmad Zacky; Ahmad, Syakif (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community service program was conducted to improve the productivity and success of young entrepreneurs at the Islamic Entrepreneur Boarding School (IEBS) in Purwakarta. The program aimed to address key challenges such as limited understanding of Islamic economic principles, managerial skills, and the application of Sharia in business practices. A total of 27 participants, comprising middle and high school students, actively engaged in the training. The activities included theoretical presentations, interactive discussions, and practical simulations using the Widget Method to enhance knowledge retention and application. The Pre-Test and Post-Test results showed significant improvement, with the average score increasing from 8.93 to 9.81. This demonstrated a better understanding of productivity concepts and financial management aligned with Islamic values. The training emphasized practical skills such as budgeting and entrepreneurial planning, enabling participants to integrate Sharia principles into their business initiatives effectively. The program also contributed to the development of a sustainable Sharia-based entrepreneurial ecosystem in the local community. Key findings highlighted the success of interactive and practical learning methods.